Tunable Second Harmonic Generation Devices with an Integrated Micro-Heater - Gan, Yi (My University, 2008)
Single-pass frequency conversion by a nonlinear optical crystal is an attractive method to generate coherent radiation in various spectral domains from ultraviolet to mid-infrared. Wavelength converters based on quasi-phase matched (QPM) periodically poled lithium niobate (PPLN) have proved to be important wavelength conversion devices for many useful applications. This thesis develops a novel integration design for temperature controlling and temperature wavelength tuning of a QPM-PPLN waveguide wavelength converter. A Cr/Pt/Au thin film alloy layer is deposited on a PPLN device with a polymer buffer layer to work as a micro-heater and a temperature sensor at the same time. The temperature of the device can be tailored by applying current to the micro-heater layer, which changes the effective period of the QPM grating and thus the QPM wavelength through the thermal optical effect (TOE). The device's temperature can be monitored by measuring the resistance change of the alloy layer. Micro-heater design and mode profile simulation are involved in the thesis. The entire device fabrication process is introduced. Both electrical and optical features of the device are characterized and discussed. In contrast to the conventional temperature tuning method based on a bulky oven, the proposed design has some excellent characteristics such as compact package size and low power consumption.
Keywords: tunable, second harmonic, generation, devices, integrated, micro-heater, fabrication